Elucidation of Volatile and Morphological Properties of Saffron (Crocus sativus) Flower as Affected by Controlled Drought Stress Induced by Polyethylene Glycol - Sevindik, Başar (Flavour and fragrance journal, 2025)
ABSTRACT Crocus sativus L., known as saffron, is one of the major crops among ornamental and medicinal aromatic plants. Polyethylene glycol (PEG) 6000 is one of the well‐known and efficient simulators used for this purpose. In this study, saffron corms were cultivated in pots containing perlite, and the PEG 6000 solution was applied at 5%, 10% and 15% concentrations. A HS‐SPME‐GC–MS system was used to elucidate volatiles of saffron flowers, and a total of 28 volatiles was detected. Safranal was measured as the most dominant volatile compound in saffron flowers, and the release of marker volatiles was dramatically increased with the increasing PEG 6000 dosage. Eucarvone was found to be an important ketone compound, Phenethyl alcohol was found to be the most abundant volatile alcohol compound. Additionally, ketones pyrrole, lactone, esters and other sulphurous components increased with PEG 6000 application. According to the morphological observations, decreases were observed in plant dry weight (PDW), plant fresh weight (PFW), corm diameter (CD), daughter corm (DCN), and flower number (FN), between the control plants and those treated with PEG 6000. However, an increase was detected in root number (RN) and root length (RL). Leaf length (LL), on the other hand, increased with a 5% PEG application but decreased with higher concentrations. PEG‐induced stress affects the morphology and aroma profile of the Crocus sativus (saffron). The effects of different dosages were investigated, and data was evaluated. Saffranal is the most important secondary metabolite of saffron and PEG‐induced stress enriched the saffranal amount in the saffron flower.